Educational data mining for mapping the comprehension of personality subject using K-Means algorithm (case study of SD Insan Mulya) - Wiwiet Herulambang; M Mahaputra Hidayat; Nabila Amanda Putri (Jurnal Mandiri IT, 2023)
The government has emphasized the importance of character education since the elementary school (SD) level by providing various subjects as an effort to build personality/character for each student. It is important for teachers and schools to know the level of understanding in their students. This research is for. This study uses the K-Means Clustering Algorithm method to help map students to the level of understanding of the Personality subject. The results of this study indicate that clustering using the K-Means Algorithm method contains 4 effective clusters in mapping the understanding of personality subjects. The result of the percentage of clusterization results with interviews is 89.39% while the percentage of software is 91.70%. The conclusions obtained in this research are the subjects of Moral Education, Religious Education, Citizenship Education are included in the Subjects that can affect the student's personality.